Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Bharaduta Jaya Sakti Jakarta Selatan - Saputra, Andre Ardian; Prasada, Dodi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of leadership style and work motivation on employee performance at PT Bharaduta Jaya Sakti, both partially and simultaneously. The research uses a quantitative approach with a population of 85 employees. The sampling technique used is saturated sampling, meaning that all members of the population were used as research respondents. Data processing and analysis were conducted using SPSS version 27 with several analytical methods, including simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, partial t-test, and simultaneous F-test. The results show that leadership style has a significant effect on employee performance with a t-value of 13.257 greater than the t-table value of 1.988 and a significance level of 0.000 < 0.05, indicating that H₀₁ is rejected and Hₐ₁ is accepted. Work motivation also has a significant effect on employee performance with a t-value of 13.735 greater than the t-table value of 1.988 and a significance level of 0.000 < 0.05, indicating that H₀₂ is rejected and Hₐ₂ is accepted. Simultaneously, leadership style and work motivation have a significant effect on employee performance with an F-value of 139.471 greater than the F-table value of 3.11 and a significance level of 0.000 < 0.05, indicating that H₀₃ is rejected and Hₐ₃ is accepted. The coefficient of determination test shows an R Square value of 0.771, meaning that leadership style and work motivation contribute 77.1% to employee performance, while the remaining 22.9% is influenced by other variables not examined in this study.